The germination and subsequent development of cocoa seedlings (Theobroma cacao L.) are subject to influence from the pregerminative methods employed - Chuquibala Checan, Beimer (2025)
In Peru, cocoa production has increased significantly, thereby establishing a prominent position for this crop in the country's agricultural landscape. The effect of different pregerminative methods on seed germination of cocoa ecotypes and their influence on seedling development in nursery were evaluated. Three cocoa ecotypes were used INDES 24, INDES 31, and INDES 67, and five pregerminative methods were applied to the seeds with mucilage, mucilage removal, tegument removal, water immersion, and immersion in Trichoderma harzianum solution. Parameters such as germination percentage GP, mean germination time GT50, mean germination rate GR50, and plant growth characteristics in terms of cotyledon height, plant height, number of leaves per plant, and stem diameter were evaluated. The results revealed that the treatments INDES 24 removal tegument, INDES 67 removal tegument, INDES 67 water immersion, and INDES 67 immersion in T. harzianum showed the best GPs of 100% at 72 h. Additionally, the INDES 67 tegument removal showed the best mean germination time and rate GT50 and GR50 with 24 h and 8 seeds/24 h, respectively. For growth parameters, INDES 67 mucilage removal showed the highest values for cotyledon height and the number of leaves per plant with 4 cm and 13.33 leaves/plant; for plant height and stem diameter, the treatments INDES 31 tegument removal and INDES 24 mucilage removal obtained the highest average values with 30.21 cm and 6.65 mm, respectively. These findings demonstrate that pregerminative methods significantly impact the germination and growth of cocoa plants. This insight can enhance cocoa propagation practices and improve the success rate of their establishment in the field.